ДАРС ЖАРАЁНИДА БОШЛАНҒИЧ СИНФ ЎҚИТУВЧИЛАРИНИНГ АХБОРОТ ТЕХНОЛОГИЯЛАРИДАН ФОЙДАЛАНИШИ МЕТОДИКАСИ - Жумамуратов, А.П. (SCIENCE and SOCIETY, 2020)
The article discusses the basic tasks of primary school teachers in the use of information technology at the lessons and developing an interest in learning, creativity and knowing the news of the world. Primary school teachers can get information using a computer during the lesson.